Absence of prenatal ultrasound surveillance: Data from the Portuguese congenital anomalies registry - Correia, Sandrina (2017)
In Portugal, prenatal care guidelines advocate two prenatal ultrasound scans for all pregnant women. Not following this recommendation is considered inadequate prenatal surveillance. The National Registry of Congenital Anomalies (RENAC in Portuguese) is an active population-based registry and an important instrument for the epidemiological surveillance of congenital anomalies (CA) in Portugal. Regarding pregnancies with CA, this study aims to describe the epidemiology of absent prenatal ultrasound scans and factors associated with this inadequate surveillance.